The Development Of Modules Based On Problem Solving with Mind Map About Blood Circulation System Material for Students Class VIII Junior High School - Salmi Halen; Lufri Lufri; Dwi Hilda Putri (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2019)
The implementation of the 2013 Curriculum is to create a creative and innovative person. One of the right approaches is Problem Solving. Circulatory system material is the material that suits the problem solving approach. Less varied teaching materials will make the learning process becomes monotonous so that learners are not interested to learn. Therefore, a research aimed to produce problem-based solving module with mind map of circulatory system material for students of class VIII SMP.This research is a development research using development procedure from Plomp with three stages: initial investigation stage, development stage or prototype, and assessment phase. The object of this research is problem solving module minded mind map, and the subject of research is teachers and learners SMPN 15 Padang.Validity results obtained an average of 86.46% with valid criteria. The results of small group practice test (small group) obtained an average of 100% very practical category. Modular practicality test obtained an average result of 83.33% with practical category, while learners of 79.32% with practical category. It can be concluded that problem solving module with mind map about circulation system material for students of class VIII SMP has been valid and practical.